High temperature fatigue characteristics of P/M and hot-forged W-Re and TZM for X-ray target of CT scanner. (5th January 2018) - Harimon, Mohd Azhar; Miyashita, Yukio; Otsuka, Yuichi; Mutoh, Yoshiharu; Yamamoto, Shinichi
Highlights: Fatigue strength at 1000 °C was evaluated by defining the failure criterion as two-times increase of initial compliance. Nucleation and propagation of multiple cracks would be a dominant fatigue damage, which would induce compliance's increase. Fatigue strengths at 1000 °C were 280 MPa, 290 MPa and 200 MPa for layered W-Re/TZM, bulk W-Re and bulk TZM, respectively. Graphical abstract: Abstract: The fatigue strengths at 1000 °C of layered W-Re/TZM, bulk W-Re and bulk TZM for x-ray target materials were successfully evaluated under load-controlled four-point bending by introducing a fatigue failure criterion as two-times increase of initial compliance. The obtained fatigue strengths at 1000 °C for layered W-Re/TZM and bulk W-Re were similar and 280 MPa and 290 MPa at 10 6  cycles, respectively, while that of bulk TZM was 200 MPa. During fatigue loading at 1000 °C, dominant fatigue damage would be multiple intergranular crack nucleation and propagation, which would induce the increase of compliance. The reasonability of the fatigue failure criterion was confirmed by the fatigue process observations and the results of room temperature fatigue tests of the specimens tested at 1000 °C up to the cycles corresponding to the fatigue failure criterion.